Imiona pochodzenia hebrajskiego w rosyjskich i polskich przysłowiach i powiedzeniach - Walczak, Maciej (Iudaica Russica, 2020)
The article deals with the analysis of the Russian and Polish paremiological units which in their structure contain the first names of Hebrew origin. Upon the proper idiom material the author shows their diversity both in the morphological and word-formative respect especially in Russian language with a high frequency of hypocoristic derivatives. The other respect is of functional and semantic character and it is reflected in the wide topical spectrum of proverbs containing Hebrew first names. Those proverbs describe not only a human beings’ character but also his behaviour, the phenomena of nature, extra-linguistic situations, customs and rituals.